Sá, Rodrix e Guarabyra: os parceiros da música bonita (1965-1980) - Macedo, Thiago Hausner de (2011)
The musical trio Sa, Rodrix and Guarabyra, and the musical style created by them, so-called country-rock, will be studied in this dissertation. The group, formed in the 1970s, had an artistic career permeated by songs that realized the social and political scenarios' changes in Brazil. Through analysis of his songs and interviews the insertion of the trio in the Brazilian MPB and in the social scene will be understood, thus coming to the processes of struggles, tensions and their stand and roundness. Approaching to the protest music and song festivals, Sa, Rodrix Guarabyra have contemplated not only the interior of an utopic brazil, touted by the military government, but a field in changes, which denounced the lifestyle of the Brazilian society of the 1960s and 1970s . Thus differing from the música sertaneja our caipira (typical rural music of the central-southern region of Brazil) - (which featured an interior look by the country music singers) - in the trio the look was reversed - came from the city to the field, thus bringing a new approach within the MPB, realizing the brazilian's interior in a perspective of the traveler. This look is accompanied by appropriation of other cultures within the between-places which was located the rural rock, causing it to be studied within the perspective of cultural hybridity, because through it is possible to evaluate the historical context to which the musicians and their compositions were inserted